Adenoid-Cystic Carcinoma of Nasal Septum and Pterygo-Palatine Fossa - Santanu Dutta; Sudipta Pal; Sirshak Dutta (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Adenoid cystic carcinoma (ACC) is an uncommon malignant tumour arising from salivary glands. It is more common in minor salivary glands, palate being the commonest site. Local recurrence, distant metastasis and perineural invasion are the common clinico-pathological features of this tumour. ACC of nasal septum and pterygo-palatine fossa is extremely rare entity with a very few reported cases in the available literature.